Efforts to Improve Islamic Education Learning Outcomes by Using Power Point Media and the Cooperative Script Learning Model at SD Negeri Keulembah - Mahmidar; Marziah, Ainal (MANDAILING GLOBAL EDUKASIA, 2025)
This research aims to improve the learning outcomes of Islamic Religious Education in Asmaul Husna's material through the use of PowerPoint media and the Cooperative Script learning model at SD Negeri Keulembah. The problem faced is the low learning outcomes and student involvement in Asmaul Husna's learning. This study uses the classroom action research method (PTK) with two implementation cycles. Each cycle includes planning, implementation, observation, and reflection. PowerPoint media is used to present material visually and attractively, while the Cooperative Script model is applied to improve interaction and cooperation between students. The results of the study showed a significant increase in learning outcomes and student activities after the implementation of the two media. The average score of students increased from 73.47 in the pre-cycle to 83.91 in the second cycle, with classical completeness reaching 91.30%. In addition, student activities in participating in learning also experienced an increase as seen from observations during the learning process. This study concludes that the combination of PowerPoint media and the Cooperative Script learning model is effective in improving the learning outcomes of Islamic Religious Education, especially Asmaul Husna material at SD Negeri Keulembah. Therefore, it is recommended for teachers to integrate the use of visual media and cooperative learning models in the teaching and learning process.